2016
DOI: 10.1097/ccm.0000000000001357
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil Gelatinase–Associated Lipocalin Predicts Survival After Resuscitation From Cardiac Arrest

Abstract: Objective In the first days after cardiac arrest, accurate prognostication is challenging. Serum biomarkers are a potentially attractive adjunct for prognostication and risk stratification. Our primary objective in this exploratory study was to identify novel early serum biomarkers that predict survival after cardiac arrest earlier than currently possible. Design Prospective, observational study Setting A single academic medical center Subjects Adult subjects who sustained cardiac arrest with return of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…918 Recent work has tested predictive value of multiple modalities, but the ideal combination is not known. 2832 Importantly, not all tests are necessary for all patients and some facilities may not offer all of these modalities. Some authors propose a stepwise approach to avoid premature WLST.…”
Section: Discussionmentioning
confidence: 99%
“…918 Recent work has tested predictive value of multiple modalities, but the ideal combination is not known. 2832 Importantly, not all tests are necessary for all patients and some facilities may not offer all of these modalities. Some authors propose a stepwise approach to avoid premature WLST.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information on serum adipokine concentrations in patients with cardiac arrest. Recently, Elmer et al showed that serum leptin concentration did not differ between nonsurvivors and survivors [30]. This is the only investigation on the role of adipokines in cardiac arrest.…”
Section: Discussionmentioning
confidence: 98%
“…An increase in NGAL within a few hours of cardiac arrest has been suggested to indicate AKI, even in creatinine-negative patients [17, 31]. Considering that NGAL increases early after ROSC, its high levels may be strongly predictive of both AKI and survival-to-hospital discharge [44]. In cardiac surgical patients, however, only L-FABP has been reported as a useful biomarker for early detection of AKI.…”
Section: Discussionmentioning
confidence: 99%